Size effect of square concrete-filled stainless steel tubular short columns under axial compression. (October 2022) - Liu, Xiaolong; Zheng, Shiyu; Xu, Zijie; Wang, Senping; Yuan, Bo
Abstract: Concrete-filled stainless steel tube (CFSST) members combine the advantages of stainless steel materials and concrete-filled steel tube (CFST) members. Therefore, it has a broad range of applications than CFST members in the marine environment and other scenarios requiring great durability and corrosion resistance. However, there are limited researches on the large-size CFSST members. In this paper, 40 square CFSST members with varying steel ratios (4 % ≤ α ≤ 10 %), widths (500 mm ≤ B ≤ 900 mm) and strength of concrete ( f c u  = 40 MPa, 50 MPa) are studied on the size effect under axial compression. The size effect on the peak axial stress, peak axial strain, composite elastic modulus and ductility coefficient are investigated. Then this paper adopted the two-way analysis of variance test (ANOVA) to analyze the data. According to the results, the peak axial strain, composite elastic modulus and ductility coefficient have size effect, but the size effect in peak axial stress does not significant. It was found that the steel ratio will also affect the size effect of CFSST members, and the size effect decreases with the increase of steel ratio. Compared with the current CFST codes, the size effect coefficient included steel ratio is introduced can better predict the ultimate bearing capacity of square CFSST short columns with low steel ratio of range of 4–10 %.